Diversity of foods among older people in northern communities of Thailand: Ways to promote health and wellness - Nisachon Bubpa; Khanitta Nuntaboot (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - Due to the increasing population and diverse lifestyles of aging people in Thailand, close examination of their needs and health care problems is required. Availability and accessibility of food affects the health and well-being of aging people in the community; therefore, to enhance their quality of life, community nurses and health care personnel must understand the variety of foods in their diet, in order to provide suitable and culturally acceptable nutrition for the elderly. The purpose of this paper is to explore the diversity of foods eaten by older people and the social, economic, environmental, and cultural contexts in which they live in the Northern region of Thailand. This is a part of a larger research project of community food management systems for the care of older people. Design/methodology/approach - Critical ethnographic research was employed during the study. The data were collected from 41 primary elderly informants and family members. The researcher collected data by conducting individual in-depth interviews, observation of activities, and focus group discussions. The text data were analyzed by content analysis. Findings - Information gathered from this research reveal nine categories of food which older people are associated with and which include: favorite foods; food provided by others; foodstuffs which should be eaten due to chronic diseases (recommended by doctor); foods to be avoided; snacks; food eaten with others (eating when socializing); food for festivals and cultural traditions; food offered for making merit; and food donated to others. Originality/value - Utilization of health data, specifically regarding individual dietary diversity, can guide community nurses and health care personnel to provide and promote health that will suit individuals and their families. Community nurses and health care personnel should be aware of the variety of older persons' diets and the importance of being able to manage and sustain their own nutritional needs. Appropriate nutrition, which is one of the social determinants of health, could improve the quality of the well-being of aging members in the community.